GRP78 inhibition enhances ATF4-induced cell death by the deubiquitination and stabilization of CHOP in human osteosarcoma - Luo, Jie; Xia, Yuanzheng; Luo, Jun; Li, Junhe; Zhang, Chao; Zhang, Hao; Ma, Ting; Yang, Lei; Kong, Lingyi (Cancer letters, 2017)
New targeted therapies are urgently needed to improve the survival of patients with refractory osteosarcoma (OS). In this study, we show that bortezomib (BTZ), not for OS treatment in the clinic, induces endoplasmic reticulum (ER) stress in U-2 OS cells. Loss of GRP78 sensitizes OS to BTZ with concomitant upregulation of ATF4 and CHOP, which indicates excessive protein synthesis. The relevance of these findings is confirmed in vivo as shown by GRP78 knockdown that delays the growth of U-2 OS xenografts in the presence of BTZ. Here, we demonstrate that MG7, a natural polyyne, can trigger apoptosis. Of note, the apoptotic response to MG7 is dependent on ATF4 but not on the upstream PERK signaling pathway. Interestingly, MG7-induced ATF4 expression does not result in an increase in the levels of CHOP. We demonstrate for the first time that GRP78 physically interacts with the N-terminal domain of CHOP to accelerate its ubiquitination in a p300-dependent manner, which in turn desensitize the tumors to ER stress. Overall, inhibiting GRP78 to strengthen the molecular mechanism of ATF4 via stabilizing CHOP protein may provide a potential vulnerability in OS. •Silence of GRP78 increases OS tumor burden in response to BTZ in vitro and in vivo.•Mechanisms of tumor suppression by MG7 involves ATF4-orchestrated ER stress.•GRP78 augments p300-dependent ubiquitination of CHOP in OS adaptation to ER stress.•CHOP expression induces oxidative stress when GRP78 activity is compromised.•Stabilization of CHOP by GRP78 knockdown enhances ATF4-mediated cell death.